Koning Sigismund en zijn gevolg in de Lage Landen – Nederlanders in Hongarije* - Bárány, Attila (Acta Neerlandica, 2017)
The 1378 Great Western Schism gave a new direction to the Luxemburgs’ traditional pro-Valois politics. The House of Luxemburg took an abrupt turn away from the French orientation, who adhered to the obedience to the Avignon pope and were seeking for new partners. At the beginning of the 15th century, even amidst the Orléans-Armagnac vs. Burgundy antagonism, Sigismund had quite good contacts with the duke of Burgundy, probably stemming from their co-operation of the crusade of Nicopolis in 1396, the Flemish participation of which the article also investigates. Sigismund came closer to Burgundy at the Council of Constance, even though they had taken an opposite stand in important issues such as the inheritance of Brabant and Luxemburg. The Luxemburgs themselves also had possessions in the Low Countries, because in the 14th century the dynasty, besides Luxemburg, also owned the Duchy of Brabant and Limburg. In the 15th century, partly because of the Burgundians gaining substantial territories, they partially opposed their rights, thereby bringing forth conflicts within the Low Countries. The article explores the relations of the House of Burgundy with the provinces of the Netherlands, especially the county of Flanders and the Flemish cities. When it comes to ‘Burgundian’ contacts, it is fundamentally taken as relations with the Low Countries, particularly Flanders. The study examines the relationships that Sigismund maintained with the political figures of the Low Countries, especially the counts of Holland and Zeeland from the House of Wittelsbach, the duke of Gelderland and Juliers/Jülich asd well as the bishops of Utrecht and Lüttich/Luik. I also wish to shed light upon contacts beyond the scene of ‘high politics’. Although we can not speak of daily relations between Hungary and the provinces of the Low Countries, there were complex contacts. Hundreds of Flemish knights took up the Cross against the Ottomans and fought at Nicopolis, the campaign of which was also funded by 24 Attila Bárány the citizens of Flanders. A range of cities embraced a rather independent political track when supplied the Emperor with ships. Flemish or Dutch craftsmen built a river flotilla for Sigismund. Relations can be come across in the clergy: Dutch masters of theology and medicine were active in Hungary, most peculiarly contributing to the development of the university in Óbuda.